DRESS syndrome and thrombotic thrombocytopaenic purpura: are they related?. (14th November 2012) - Sandouk, Zahrae; Alirhayim, Zaid; Khoulani, Dania; Hassan, Syed
Abstract : A middle-aged man diagnosed with a drug reaction with eosinophilia and systemic symptom (DRESS) syndrome, secondary to phenytoin use, subsequently developed thrombotic thrombocytopaenic purpura. The patient improved with steroids and plasmapheresis. Their diagnosis can be challenging, and an early recognition and treatment are critical owing to their high mortality rates. Both diseases are thought to be of an autoimmune origin, and a potential relationship between them led to the consideration of the DRESS syndrome as an aetiology for thrombotic thrombocytopaenic purpura in this case. We concluded that two possibilities exist: some type of antibody developed during the clinical presentation of DRESS syndrome and subsequently resulted in an inhibition of a disintegrin and metalloproteinase with a thrombospondin type-1 motif, member 13 (ADAMTS13) leading to thrombotic thrombocytopaenic purpura, or perhaps this patient's autoimmune predisposition to thrombotic thrombocytopaenic purpura contributed to the drug reaction.